In Vitro Gene Expression Dissected: Chemostat Surgery for Mycobacterium Tuberculosis. Issue 4 (2002) - James, Brian W.; Bacon, Joanna; Hampshire, Tobias; Morley, Kim; Marsh, Philip D.
Abstract : A unique approach, combining defined and reproducible in vitro models with DNA microarrays, has been developed to study environmental modulation of mycobacterial gene expression. The gene expression profiles of samples of Mycobacterium tuberculosis, from independent chemostat cultures grown under defined and reproducible conditions, were found to be highly correlated. This approach is now being used to study the effect of relevant stimuli, such as limited oxygen availability, on mycobacterial gene expression. A modification of the chemostat culture system, enabling largevolume controlled batch culture, has been developed to study starvation survival. Cultures of M. tuberculosis have been maintained under nutrient-starved conditions for extended periods, with10 6 –10 7 bacilli surviving in a culturable state after 100 days. The design of the culture system has made it possible to control the environment and collect multiple time-course samples to study patterns of gene expression. These studies demonstrate that it is possible to perform long-term studies and obtain reproducible expression data using controlled and defined in vitro models.